Operationalization of parameters and diagnostics of personal identity - Yuliya E. Makarevskaya; Zinaida I. Ryabikina (Теоретическая и экспериментальная психология, 2023)
Background. In modern conditions of existence, it is difficult to talk about the stability of a person's identity: it fluctuates, transforms, multiplies, and disappears. The instability of identity is manifested not only in the problems of self-determination, adaptation, self-realization, but also in the risks of losing the opportunity to be a subject of one's own life, to consciously identify and responsibly present oneself to the outside world. The research shows that personal identity provides internal harmony and stability of the subject. However, currently we don’t have a corresponding diagnostic tool with satisfactory psychometric indicators, which makes it difficult to study, monitor, and determine available resources for maintaining the stability of the personality in a changing world. Objective. The study was aimed at creation and psychometric verification of the methodology for diagnostics of personal identity, providing empirical verification of its structure, assessment of validity, internal consistency, and retest reliability. Methods. The study implemented the methods of semi-structured interview, unfinished sentences, survey, expert assessments, calculation of statistical correlation coefficients and comparison of averages, factor analysis as well as standardization procedures and psychometric checks of validity and reliability of the test. Sample. The total volume of the research measurements was carried out on a sample of 1,384 people (36.8% men, 63.2% women) aged 13 to 90. Results. The results of psychometric verification of the test (N = 500) showed a satisfactory degree of internal consistency, retest reliability of the scales (factors) “reflected Self”, “unique Self” and variability of the values on the “personal Self” scale. Conclusion. The methodology can be used in the scientific and practical activities of psychologists specializing in the problems of personality psychology, in the diagnostics of self-identification processes of personality in various life situations and in different periods of life, while determining the stability of personality in conditions of social change.